Evaluation of spot urinary albumin-creatinine ratio as a screening tool in prediction of preeclampsia - Shaily Agarwal; Pratibha Devi; Renu Gupta; Pratima Verma; Apoorva Agarwal (Barpeta Obstetrics and Gynaecological Society, 2022)
Objective: The prime objective of this study was to determine the effectiveness of preeclampsia prediction in asymptomatic cases with a spot urinary albumin creatinine ratio measured between 20 to 24 weeks of gestation. Materials and methods: The study included 156 women with a singleton pregnancy, normal renal function, and no evident proteinuria, attending antenatal clinics between 20 to 24 weeks of gestation at GSVM Medical College. Spot urine samples were taken between 20-24 weeks of gestation and urinary albumin was determined by the Biuret method and creatinine measured by modified Jaffe's method. Results: Preeclamptic patients who were asymptomatic in early pregnancy and developed preeclampsia, later on, yielded significantly higher spot UACR values than the normal ones. UACR value satisfactorily predicted preeclampsia well before the onset of clinical manifestations with high sensitivity and specificity. Especially, lower UACR values accurately corresponded to normotensive cases with a negative predictive value of 92%. Out of 156 subjects, 24 developed preeclampsia. The sensitivity and specificity of UACR in predicting the development of preeclampsia were 62% and 84% respectively. Conclusion: The spot urine ACR test has the potential to predict preeclampsia and thereby reduce maternal and fetal mortality and morbidity by early intervention and intensive clinical follow-up. Thus it is an excellent predictor of preeclampsia.